MANUAL PRÁTICO PARA GESTÃO DE PATRIMÔNIO MÓVEL DA UNIVERSIDADE ESTADUAL DO CENTRO-OESTE - Pedroso, Cristian (2023)
The public administration is subject to several changes that occur through laws, decrees, regulations, and orders, which have a significant impact on the entire structure of the public sector. Asset management has been one of the areas of public administration that has undergone significant changes in legislation in recent years, including the implementation of a computerized system for managing movable assets for the agencies of the State of Paraná, including those of the indirect administration. The State University of the Midwest (UNICENTRO) is a higher education institution located in the central region of the State of Paraná, present in six municipalities (Guarapuava, Irati, Chopinzinho, Coronel Vívida, Pitanga, and Prudentópolis). The quantity of movable assets registered in the internal management platform, the University Management System (SGU), is about 85 thousand items. The way the data was registered represents a challenge for the migration in a reliable manner to the system proposed by the state. Normatives such as Decree No. 8.955/2018 established deadlines for the direct and indirect administration agencies to introduce accounting procedures according to Law No. 8.485/1987. In addition to this situation, the Directorate of Assets (DIRPAT), which is the Administrative Unit responsible for asset management at UNICENTRO, underwent a personnel restructuring. This presented an opportunity to conduct research in the area of organizational processes, using the institutionalization strategy to institutionalize the processes involving movable asset management, mainly due to the implementation of the Mobile Asset Management System (GPM), as the systems are considerably different. The research is characterized as participative, and documentary analysis was also used. Regarding the processes, flowcharts were developed to depict how they were previously executed and then remodeled according to the necessary adaptations. To remodel the processes, materials from the State Department of Assets (DPE) and the Department of Administration and Pensions of Paraná (SEAP), which is responsible for instructing on methodologies within the state's context, were used. As a result of this technical report, the Manual of Mobile Asset Management Practices at the State University of the Midwest was obtained. It contains conceptual and instructional information, and the flowcharts were employed to familiarize employees with the stages involved in each process. Tutorial screens, developed by DPE, were also used to guide each registration process. Finally, a draft Resolution was elaborated to institutionalize the manual at UNICENTRO, establishing it as an instructional tool for possible future teams working in DIRPAT.